Methylene Blue Biosorption using sawdust of the Apuleia Leiocarpa genus (Research, Society and Development, 2020)
The adsorption is promising technique for dyes removal from textile effluents, among them methylene blue (AM). This technique is even more attractive when using low cost materials such as sawdust (PS) as adsorbents. The aim of this work was to study the use of sawdust powder of the Apuleia Leiocarpa as adsorbent material in the methylene blue (AM) biosorption from textile effluents. Experimental tests were carried out in stirred tank to determine the equilibrium isotherm and the kinetics of adsorption, fitting the most usual models in literature. The fixed bed tests were conducted to obtain the rupture curves, which correlate the dye concentration with time, under different conditions of initial solution concentration and feed flow rate. The results showed that the equilibrium isotherm was favorable, indicating the PS as a good adsorbent, with a maximum adsorption capacity of 61.8 mg/g. The Yan model satisfactorily represented the adsorption process in the fixed bed. The higher adsorption capacity occurred working with a concentrate solution at the lower feed flow rate, which presented a higher useful percentage of bed, indicating the PS as good adsorbent to remove AM from liquid effluents.